Ontogenetic features of the formation of the mandible structure. - O. M. Slobodian; L. P. Lavriv; V. O. Kostyuk (Морфологія, 2016)
Morphologists of the 21st century are trying to consolidate and extend links between morphology and clinical research. Investigation of the anatomical structure of the mandible is now one of the urgent problems of modern dentistry, plastic surgery, anthropological and forensic practice. Along with advances in the study of human skull as a whole data on the mandible are fragmented and incomplete. It is important to determine gender, age and individual features of the mandibular characteristics. Further study of mandibular area provides the opportunity to correct data for validation ultrasound and magnetic resonance tomography of the skull morphometry, and can serve as a basis for determining critical periods of the face development.